Associations between air pollution and hospitalization for cardiovascular disease: a time series study in Nanchong - Zaiyong Zheng; Zaiyong Zheng; Zaiyong Zheng; Yanman Li; Qinglu Jiang; Fangfang Zang; Fangfang Zang; Fangfang Zang; Yang Yu; Yang Yu; Yang Yu; Rongchuan Yue; et al. (Frontiers in Public Health)
ObjectiveTo investigate the acute effects of air pollution on the daily hospitalizations for cardiovascular disease.MethodsData of daily hospitalization for cardiovascular disease were collected from the hospital electronic health record system in Nanchong. The air pollutants and meteorological data were obtained from the fixed monitoring stations. We performed over-dispersed Poisson regression incorporated with distributed lag models to assess associations between short-term exposure to air pollutants and the risk of cardiovascular disease hospitalizations.ResultsA total of 373,390 hospitalizations for cardiovascular diseases were identified. We found that a 10 μg/m3 increase in 7-day average concentrations of PM2.5 and PM10 was associated with 1.15% (95%CI: 0.55–1.76%) and 0.51% (95%CI: 0.19–0.82%) higher cardiovascular disease admissions. NO2 presents the largest adverse effect. The risk of cardiovascular disease admission increased by 6.26% with per 10 μg/m3 increase in NO2 for lag07.ConclusionShort-term exposures to high concentrations of air pollutants increased the risk of hospitalization for cardiovascular disease. Policymakers need to develop policies and strategic plans to combat air pollution.